Modalities of liberalization and preferential treatment for developing countries: the pending issues in the negotiation of services in the FTAA - García, Santiago (2016)
Focusing on the modalities of service trade liberalization and the principle of preferential treatment for small developing economies, this article studies the possibilities and conditions of service trade negotiations within the FTAA. The author takes both elements as crucial factors influencing the final results of the negotiation process, and suggests several recommendations from the perspective of a "positive agenda'.